Lived Experiences of Athletes' Dual Career: A Phenomenological Study - Sinag, Jay Mark D.; Mortejo, Alonzo L. (Universitas Negeri Padang, 2024)
The study aims to examine to investigate the variables influencing the dual role of student athletes. This qualitative study used a phenomenological research design which examined the needs of student athletes at particular state colleges and universities performing dual roles . The researchers discovered that obstacles that make it difficult for individuals to fulfill their obligations in both athletics and academics are time management, money problems, and internal issues such as parental and teachers support. Policy for counselling interventions among athletes is necessary for development sports program.